Colorimetric Sulfide Sensing: Au/AgI Dimeric Nanoparticles for Highly Selective and Sensitive Colorimetric Detection of Hydrogen Sulfide (Adv. Funct. Mater. 26/2018). (25th June 2018) - Zeng, Jingbin; Li, Min; Liu, Ao; Feng, Fan; Zeng, Teng; Duan, Wei; Li, Mengmeng; Gong, Mingfu; Wen, Cong‐Ying; Yin, Yadong
Abstract : The warrior with a shield represents a unique Au–AgI dimeric nanostructure that is developed for sensitive and selective colorimetric detection of H2 S. Upon attack by H2 S, AgI (the shield) converts to Ag2 S, inducing a plasmonic shift of the connected Au nanoparticle (the warrior). The Au nanoparticle changes its color depending on the concentration of the sulfide, thus enabling a naked‐eye readout, as described by Jingbin Zeng, Yadong Yin, and co‐workers in article number1800515 .